Heart Rate and Anthropometrical Study of Nepalese International Boxing Players - Amatya, Diwakar Lal; Maharjan, Pradip (Mangal Research Journal, 2022)
The present study aimed to measure the HR response of boxing players during the four rounds of a punching before and after training to determine effectiveness of the training. Five international male Boxers who were participating in Asian Boxing Championship were selected with purposive sampling method. The data were collected during preparation camps for the championship. Each athlete was tested for various Anthropometric measurements necessary for the exact decimal ratings of Endomorphy, Mesomorphy and Ectomorphy equations developed by Carter and Heath (1990). Lafayette Skinfolds caliper has been used to measure the skin folds and for bone width measurement. For the Body Composition calculation, Drinkwater and Ross fractionation procedure (1980) was followed using Phantom model. Cardio-sport Heart Rate monitor was used to measure heart rate. Maximum heart rate and recovery heart rate were measured before and after training in 7 weeks interval on the same samples. Nepalese Boxers were observed with average somatotype of 1.97 – 4.49 – 2.23 falling in Ectomorphic – Mesomorph category. Nepalese International Boxer’s average age, height, body weight is 23.83 (S.D. 2.23), 168.1 cm (SD 8.5 cm) and 60.0 kg (SD 9.35) respectively. Nepalese Boxers are having 9.06 % body fat percentage and muscle mass 46.9 %. This study found the participants had good endurance capacity and improved their fitness level after 7-week training. This study suggested that they should give more emphasis in weight training. Future studies should conduct on larger samples including other sports and parameters.